Finite element modeling and probabilistics analysis of prestressed inversted T-beam with web opening - Tie, Ming (2021)
Recent trends of structural mechanics applications in finite element analysis demonstrate an increasing demand for efficient analysis tools. This thesis presents a probabilistic analysis approach applied in finite element analysis for modelling prestressed inverted T-beams with web openings structure used in building service system (mechanical, electrical, communications, and plumbing). Prestressed concrete structures are commonly designed to satisfy criteria of serviceability and safety. In order to ensure the serviceability requirement it is necessary to predict the response of these structures under service loads. However, calculation of deflections of prestressed concrete structures is complicated by several factors, including shrinkage and creep of concrete, relaxation of prestressing reinforcement and cracking. Due to the inherent uncertainties in nature, it is difficult to determine the related parameters precisely. Material and geometric properties of the cracked prestressed concrete structure and load systems possess different degrees of uncertainties. Uncertainties of material properties could arise because of limited site investigations and limited material laboratory test and in accurate formula for correlating various material parameters. Uncertainties of geometric properties could be due to variations during fabrication and erection of the structure. The experimental program reported in this study was in the literature review about four prestressed inverted T-beams with circular web openings tested to failure to evaluate the openings' effect on various beam behaviours. Using ANSYS, finite element models were developed to simulate beam deflection behaviour. Comparison of analytical results with the available experimental results for load-deflection relationships showed good agreement between both results. Probabilistic analysis methodology could predict the response (i.e. deflection, stress, strain etc) due to various combination of input variables (i.e. opening radius, Poisson`s ratio, modulus of elasticity, etc). Probabilistic methodology applied in finite element analysis provides an alternative ways to structural analysis of preststressed inverted T-beams with web openings to achieve a robust and reliable design in a more efficient way. In this thesis, Monte Carlo simulation and Latin Hypercube simulation (LHS) was used to analyze the effect of parameter uncertainty for the prestressed inverted T-beams with web openings. From the analysis results, it was observed that the changes in prestressing force, ultimate tensile strength of prestressing steel, elastic modulus of prestressing steel and beam width tend to be the most influencing parameters, which need to be tightly controlled. As a result, from deterministic analysis and probabilistic analysis, it was found that probabilistic analysis tends to be closer to reality than deterministic methods and gives a way of designing for quality.